2011
DOI: 10.1111/j.1559-1816.2011.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Is In! Implicit Exercise and Sedentary-Lifestyle Bias Held by In-Groups1

Abstract: This research examined implicit exercise‐related bias between exercising groups. Participants (N = 53) completed an Implicit Association Test with neutrally valenced exerciser or couch potato exemplars. Participants who explicitly identified as exercisers had greater positive bias toward exercisers and against couch potatoes than did participants who identified as nonexercisers. Similarly, participants who reported greater exercise had significantly greater positive bias toward exercisers than did participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…There was a moderate level of heterogeneity (I 2 = 51%). Two univariate outliers (Oliver & Kemps, 2018;Berry et al, 2011) were identified with the Grubbs tests performed on the 55 available effect sizes. In the aggregated analysis, one multivariate outlier (Oliver & Kemps, 2018) was identified (see in supplemental results [Insert Figure 2 about here]…”
Section: Association Between Implicit Attitudes and Physical Activitymentioning
confidence: 99%
“…There was a moderate level of heterogeneity (I 2 = 51%). Two univariate outliers (Oliver & Kemps, 2018;Berry et al, 2011) were identified with the Grubbs tests performed on the 55 available effect sizes. In the aggregated analysis, one multivariate outlier (Oliver & Kemps, 2018) was identified (see in supplemental results [Insert Figure 2 about here]…”
Section: Association Between Implicit Attitudes and Physical Activitymentioning
confidence: 99%
“…Sixteen studies were designed to investigate automatic affective processes. Six studies examined the differences in automatic affective reactions to stimuli associated with physical activity between physically active and inactive individuals [92][93][94][95][96][97]. Five of these studies showed the expected associations between automatic affective reactions and physical activity, but the effects sizes were highly variables (see table 1).…”
Section: Automatic Affective Processesmentioning
confidence: 99%
“…Results showed that physically active individuals were faster at categorizing positive target words after exercise primers, whereas inactive students were faster with negative words (d = 0.59). Using an IAT contrasting words associated with physical activity (e.g., workout, cross-train, run) and sedentary behaviors (sit, rest, snooze), a study revealed that individuals who were explicitly identified as exercisers had more positive automatic affective reactions toward exercise, as compared to non-exercisers (d = 0.81) [93]. Additionally, participants who reported greater habitual levels of physical activity also had more positive automatic affective reactions toward exercise compared to participants who reported less habitual physical activity levels.…”
Section: Automatic Affective Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a number of studies have linked health protective behaviors and implicit attitudes. For example, implicit attitudes have been related to condom use (Czopp, Monteith, & Zimmerman, 2004;Stacy, Ames, Ullman, Zogg, & Leigh, 2006), physical exercise (Berry, Spence, & Clark, 2011;Keatley, Clarke, & Hagger, 2009), and healthy eating (Papies, Stroebe, & Aarts, 2009).…”
Section: Implicit Associationsmentioning
confidence: 99%